PERBANDINGAN TEKNIK INTERPOLASI DEM SRTM DENGAN METODE INVERSE DISTANCE WEIGHTED (IDW), NATURAL NEIGHBOR DAN SPLINE - Pasaribu, Junita Monika; Haryani, Nanik Suryo (Institut Teknologi Sepuluh Nopember, 2012)
Flood simulation model requires input data, such as 10 meters spatial resolution of DEM (Digital Elevation Model) which is higher than the available data DEM SRTM (Shuttle Radar Topography Mission). Detail DEM can be made using interpolation method of height points. The research has two purposes, first is to generate DEM with 10 meters spatial resolution and the second is to study the differences of the DEM interpolation result by using Inverse Distance Weighted, Natural Neighbor and Spline. Height points of DEM SRTM were extracted and converted into point format data, and then it was used as the input data in interpolation process. The quality of DEM from the interpolation result was influenced by weighting model used in the process, therefore the effects of weighting model on height value obtained by the interpolation result was also observed. The result indicates that the best DEM with 10 meters spatial resolution can be produced using Natural Neighbor and Regularized Spline type method. The DEMs have low error value, smooth surface and closer appearance to the earth's surface observed visually from Google Earth. Another influential factor to improve the quality of DEM in interpolation process, is the height points of the input data should be evenly distributed over the study area.